2016
DOI: 10.1039/c6ra13911f
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic aminopyrazine–reduced graphene oxide coated carbon cloth electrode as an active bio-electrocatalyst for extracellular electron transfer in microbial fuel cells

Abstract: In the present study, a low molecular heterocyclic aminopyrazine (Apy)–reduced graphene oxide (r-GO) hybrid coated carbon cloth (r-GO–Apy–CC) was employed as an active and stable bio-electro catalyst in a microbial fuel cell (MFC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The anode was made up of a low molecular heterocyclic aminopyrazine (Apy)-reduced graphene oxide (r-GO) hybrid coated CC (r-GO-Apy-CC; 25 cm 2 ). The anode material was selected based on one of our previous studies [23], where the r-GO-Apy-CC electrode was found to exhibit excellent bioelectrocatalytic activity for both bacterial adhesion and current generation. Electrodes such as CC (25 cm 2 ; Synergic India Pvt.…”
Section: Mfc Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anode was made up of a low molecular heterocyclic aminopyrazine (Apy)-reduced graphene oxide (r-GO) hybrid coated CC (r-GO-Apy-CC; 25 cm 2 ). The anode material was selected based on one of our previous studies [23], where the r-GO-Apy-CC electrode was found to exhibit excellent bioelectrocatalytic activity for both bacterial adhesion and current generation. Electrodes such as CC (25 cm 2 ; Synergic India Pvt.…”
Section: Mfc Constructionmentioning
confidence: 99%
“…Pang et al [20] have reported an MFC employed with graphite felt coated conductive polypyrrole that reduces the cathodic overpotential and improves the electron shuttling at the cathode-catholyte interface for Cr 6+ reduction. Nevertheless, their long-term applications are still limited due to complicated synthesis methods, poor dispersibility, weak stability, and low conductivity [23].…”
Section: Introductionmentioning
confidence: 99%
“…The anode was made up of a low molecular heterocyclic aminopyrazine (Apy)-reduced graphene oxide (r-GO) hybrid coated CC (r-GO-Apy-CC; 25 cm 2 ). The anode material was selected based on one of our previous studies [23], where the r-GO- Fluctuations in the pH of the two chambers were monitored by using online indicators ( Fig. 1b).…”
Section: Mfc Constructionmentioning
confidence: 99%
“…Pang et al, 2013 [21] have reported an MFC employed with graphite felt coated conductive polypyrrole that reduces the cathodic overpotential and improves the electron shuttling at the cathode -catholyte interface for Cr 6+ reduction. Nevertheless, their long-term 75 applications are still limited due to complicated synthesis methods, poor dispersibility, 76 weak stability and low conductivity [22]. 77…”
Section: Introductionmentioning
confidence: 99%